Engine modelling of a single cylinder diesel engine fuelled by diesel-methanol blend - Erdiwansyah, .; Leman, A.M.; Khoerunnisa, F.; Sardjono, R. E.; Munawir, .; Maulana, M. I.; M. S. M., Sani (IOP Publishing, 2019)
Performance on diesel engines with various combustion chamber sizes and fuel injection require effective handling so that the root combustion process in large diesel engines is timely. This study compares the experimental data with simulation through the single cylinder diesel modelling using GT-Power software. This simulation utilises parameters in diesel engines of 1000 and 2000 rpm speeds with methanol and diesel fuels. This modelling aims to develop a single cylinder diesel engine by measuring all components on the machine. The comparison between the simulation results and experimental data indicate similar collaboration with a difference about 5%–10%. Based on the results, the modelling of developed machine shows that simulation using GT-Power software is able to successfully validate all machine data parameters up to 90%. This simulation result can be expressed accurately similar to the experimental results and can be used as standardization for a single cylinder diesel engine design.